CONSTRUCTED WETLANDS DENGAN TUMBUHAN ECENG GONDOK (Eichhornia crassipes) SEBAGAI ALTERNATIF PENGOLAHAN AIR LIMBAH INDUSTRI TAPIOKA - Eko Siswoyo; Faisal Faisal; Nur Kumalasari; Kasam Kasam (Jurnal Sains & Teknologi Lingkungan, 2020)
Some problems with wastewater treatment that often arise are the high cost and complexity of wastewater treatment plants. This condition often causes various environmental problems because of dispossal of wastewater to the water bodies without any proper treatment, for example wastewater from the tapioca industry. Constructed Wetlands are one method of treating wastewater that is easy, inexpensive and has good capabilities. This study examines the ability of wetlands to treat tapioca industry wastewater. The type of reactor that was built in the wetlands used in this study is Free Water Sutface (FWS) in batch system with water hyacinth plants (Eichhornia crassipes). BOD, COD, TSS and Cyanide in tapioca industrial wastewater with several concentrations ranging from 20, 40, 60, 80 and 100% were applied in the current study. While the observation time in this study was 10 days. Samples were taken on days 0, 2, 4, 6, 8 and 10. The results of this study showed that wetlands were able to reduce levels of BOD, COD, TSS and cyanide up to 97.9%, 84.4%, 45.6% and 99.9%, respectively. These results indicate that wetlands built with water hyacinth plants have excellent ability to reduce pollutants in tapioca industry wastewater, so that one alternative can be used to overcome the problem of environmental pollution due to wastewater disposal in Indonesia.